2020
DOI: 10.1079/hai.2020.0001
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Assisted Activities for Children with Autism Spectrum Disorders: Parent Insights

Abstract: This exploratory study was designed to investigate parental perceptions of animal-assisted activities for children diagnosed with autism spectrum disorder (ASD). In-depth interviews with 10 families provided insight into the possible mechanisms by which human-animal interactions impact socioemotional behaviors for children ASD. Parents suggested that interactions with animals are qualitatively different than interactions with humans allowing for enhanced communication and connection through reductions in anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…Our findings demonstrating positive perceptions toward AAIs further align with previous studies that have evaluated specific school-based AAIs and have found positive perceptions among parents and key stakeholders (i.e., counselors and teachers) [ 10 , 11 , 12 , 13 , 14 , 15 ]. Pet owners in our sample population had more positive attitudes toward animals, which supports early literature around closeness to animals and how pet ownership is important in shaping attitudes toward animals [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings demonstrating positive perceptions toward AAIs further align with previous studies that have evaluated specific school-based AAIs and have found positive perceptions among parents and key stakeholders (i.e., counselors and teachers) [ 10 , 11 , 12 , 13 , 14 , 15 ]. Pet owners in our sample population had more positive attitudes toward animals, which supports early literature around closeness to animals and how pet ownership is important in shaping attitudes toward animals [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…One hypothesis relates to the human-animal bond, meaning the relationship between the canine and pediatric participants in AAT, indicating that this bond is a vital part of the therapeutic process and that behaviors would not be modifi ed without the inclusion of canines in participants' plans of care. 21,22 Th is phenomenon is certainly supported in this case study, as the canine was the target of most of Caleb's recorded interactions. Animals may act as a "transitional object" in AAT sessions, allowing children with ASD to practice social skills in a safe environment and then apply learned behavior outside the clinical setting.…”
Section: ■ Conclusionsupporting
confidence: 65%
“…Moreover, further insight into the mechanism of action by which animal interaction produces therapeutic effects for children with ASD who are participating in AAT sessions is required to create evidence-based intervention programs. One hypothesis relates to the human-animal bond, meaning the relationship between the canine and pediatric participants in AAT, indicating that this bond is a vital part of the therapeutic process and that behaviors would not be modified without the inclusion of canines in participants' plans of care 21,22. This phenomenon is certainly supported in this case study, as the canine was the target of most of Caleb's recorded interactions.…”
Section: Discussionmentioning
confidence: 67%